Pemberian Posisi Semi Fowler untuk Meningkatkan Saturasi Oksigen pada Pasien Congestive Heart Failure di Ruang Intensive Care Unit - Febi Kusuma Nugraha; Saktika Aisya Hadyantari; Dian Hudiyawati; Endar Sulistyo (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Congestive Heart Failure (CHF) is a medical condition that affects various body systems and causes the heart to be unable to pump blood properly to meet metabolic needs. To increase oxygen levels in CHF patients, one approach is to change body position. This study used a descriptive method to evaluate the impact of the semi-Fowler position on oxygen levels. This study involved 10 patients in the ICU Room of RSUD Ir. Soekarno Sukoharjo, with the semi-Fowler position at a 45° angle applied for 15 minutes after eating at 13:00, from 23 to 25 May 2023. Patients who met the inclusion criteria were those with oxygen saturation <95%, while patients who refused or experienced complications were not included. The instruments used included the SOP for the 45° semi-Fowler position and the Mindray PM 60 oximeter. The results showed that the 45° semi-Fowler position could increase oxygen saturation by around 2%, with a variation in increase between 2% and 4%. In conclusion, the 45° semi-Fowler position can increase oxygen levels by around 3-4% in CHF patients, as well as help reduce shortness of breath.